Delhi Metro : airport express line - Jacob, Joshy, (SAGE business cases., 2015)
The Delhi Metro Rail Corporation (DMRC) suggested the construction of a dedicated express metro line from the city center to the airport, which had just been handed over to a private party for development. Among the options available to the DMRC was private participation in the project. The structuring had to be such that the project would be completed by the Commonwealth Games deadline of September 2010. The case provides an opportunity to discuss the various structuring options for a public-private-partnership (PPP), the criteria for assessment, and financial analysis in the context of a large infrastructure project.